2021
DOI: 10.3389/fphar.2021.688625
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor Inflammatory Microenvironment in Lung Cancer

Abstract: Lung cancer is the most common and fatal malignant tumor in the world. The tumor microenvironment (TME) is closely related to the occurrence and development of lung cancer, in which the inflammatory microenvironment plays an important role. Inflammatory cells and inflammatory factors in the tumor inflammatory microenvironment promote the activation of the NF-κB and STAT3 inflammatory pathways and the occurrence, development, and metastasis of lung cancer by promoting immune escape, tumor angiogenesis, epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 114 publications
1
71
0
Order By: Relevance
“…It also includes exosomes and apoptotic bodies in which they are known as an extracellular vehicle (EVs). Moreover, TME has special unique features including hypoxia and acidic environment [20][21][22]. The lung TME plays an imminent role in cancer cell resistance by interfering with the pharmacokinetic distribution of the anti-cancer agent [23].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…It also includes exosomes and apoptotic bodies in which they are known as an extracellular vehicle (EVs). Moreover, TME has special unique features including hypoxia and acidic environment [20][21][22]. The lung TME plays an imminent role in cancer cell resistance by interfering with the pharmacokinetic distribution of the anti-cancer agent [23].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…TME consists of a heterogeneous population of cancer cells, immune cells, vessels, stroma, signaling mediators and extracellular matrix proteins (8). The presence of a chronic inflammatory environment in lung cancer (9) may alter or deviate immune cell differentiation, resulting in an imbalance of anti-tumor activity, thus favoring tumor evasion (8) and later on, resistance to ICI (10). In this context, TME might represent a relevant source of predictive biomarkers for ICIs, as well as a potential target for novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological and clinical studies have shown a strong relationship between lung cancer, inflammatory microenvironment, and chronic infection [39], as well as between colorectal cancer and chronic inflammatory diseases [24]. In pancreatic cancer, an extensive stromal remodeling, with inflammatory cells and fibrotic scars, is also a hallmark of this type of cancer.…”
Section: Introductionmentioning
confidence: 99%